1997
DOI: 10.1126/science.275.5297.206
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Interferon-γ Inducing Factor Mediated by Interleukin-1β Converting Enzyme

Abstract: The interleukin-1beta (IL-1beta) converting enzyme (ICE) processes the inactive IL-1beta precursor to the proinflammatory cytokine. ICE was also shown to cleave the precursor of interferon-gamma inducing factor (IGIF) at the authentic processing site with high efficiency, thereby activating IGIF and facilitating its export. Lipopolysaccharide-activated ICE-deficient (ICE-/-) Kupffer cells synthesized the IGIF precursor but failed to process it into the active form. Interferon-gamma and IGIF were diminished in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
749
1
9

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,092 publications
(780 citation statements)
references
References 26 publications
21
749
1
9
Order By: Relevance
“…Other caspases, particularly those cleaving intracellular proteins associated with apoptosis, were at least 100-fold less active than caspase-1. 9 Similar studies with IL-18-deficient mice revealed its role in NK cell activity and cytokine induction. 12 A caspase-1-independent pathway of IL-18 secretion from FasL-stimulated macrophages was recently demonstrated, suggesting that FasL may induce alternative mechanisms for production of IL-18.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Other caspases, particularly those cleaving intracellular proteins associated with apoptosis, were at least 100-fold less active than caspase-1. 9 Similar studies with IL-18-deficient mice revealed its role in NK cell activity and cytokine induction. 12 A caspase-1-independent pathway of IL-18 secretion from FasL-stimulated macrophages was recently demonstrated, suggesting that FasL may induce alternative mechanisms for production of IL-18.…”
mentioning
confidence: 79%
“…Injection of P. acnes into caspase-1-deficient mice, followed by LPS challenge resulted in low levels of circulating IFNcompared with wild-type mice. [8][9][10][11] Injection of IL-18 restored the IFN-production in response to LPS in the caspase-1-deficient mice, 9 further supporting the concept that caspase-1 is involved in the production of active IL-18. Other caspases, particularly those cleaving intracellular proteins associated with apoptosis, were at least 100-fold less active than caspase-1.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…[12][13][14][15] These mice have a defect in the maturation of proIL-1b and proIL-18 and are resistant to the lethal effect of endotoxins. IL-18 was first described as an endotoxininduced factor that stimulates the production of interferon-g by splenocytes.…”
Section: Caspase-1 and It Substrate Il-1bmentioning
confidence: 99%
“…13 It has been reported that other proteases are able to cleave IL-18 to inactive forms: caspase-3 acts on both proand mature IL-18, thereby generating a biologically inactive molecule of 14 kDa. 14 In previous studies, it has been proposed that both IL-18 and caspase-1 are produced by normal colon epithelium, where IL-18 may be involved in the regulation of the local immune response through IFN-␥ induction. By contrast, caspase-1 was no longer expressed in colon carcinoma, suggesting that the disappearance of mature IL-18 is associated with tumor progression in human colon cancer.…”
mentioning
confidence: 99%